Effect of garlic extract on weight loss and gut microbiota composition in obese women: A double-blind randomized controlled trial - Ettehad-Marvasti, Fateme; Ejtahed, Hanieh-Sadat; Siadat, Seyed-Davar; Soroush, Ahmad-Reza; Hoseini-Tavassol, Zahra; Hasani-Ranjbar, Shirin; Larijani, Bagher (Frontiers in Nutrition, 2022)
Objective: From a nutritional perspective, garlic extract could be a prebiotic product, which is useful for obese subjects, and one of its health-promoting underlying mechanisms is modulating gut microbiota composition. In this randomized double-blind clinical trial, the goal was to determine the effect of Allium (garlic extract) on anthropometric indices and gut microbiota composition in obese women following a low-calorie diet. Methods: Forty-three obese women were randomly divided into garlic extract (400 mg Allium sativum powder containing 1100 mcg allicin/tablet) or placebo groups. During the 2 months of the study, each participant took two tablets per day. At the beginning and at the end of the clinical trial, anthropometric measurements were done and blood and faecal samples were collected. We evaluated the gut microbiota composition using quantitative real-time PCR. Results: 16 subjects in each group completed the 2-month trial. Allium and placebo groups’ participants had mean ages of 37.8± 7.4 and 34.2 ± 6.8 years, respectively (P>0.05). Baseline body mass index (BMI) was significantly different between groups, subjects in the placebo group had lower BMI compared with the Allium group (P<0.05). Allium and placebo caused a 1.7% and 2.7% decrease in BMI from the baseline values, respectively (P<0.01). Fasting insulin level significantly decreased in the both groups (P < 0.01). Level of homeostasis model assessment of insulin resistance (HOMA-IR) has decreased significantly in the Allium group (P=0.007). The frequency of Akkermansia had decreasing trend while the abundance of Faecalibacterium and Bifidobacterium showed increasing trend in the Allium group. Conclusions: In the both groups, a decrease in BMI and other anthropometric indices has been observed. Despite weight loss after following a low-calorie diet and taking Allium, slight changes have been shown in the composition of gut microbiota in obese women. Trial registration: This trial was registered in the Iranian Registry of Clinical Trials (IRCT) (code: IRCT090420001825N2). Keywords: Gut microbiota, Clinical trial, Obesity, Allium sativum, Prebiotic